Implementasi Prinsip Restorative Justice Dalam Penanganan Tindak Pidana Pencemaran Nama Baik Melalui Media Sosial - Dyah Ayu Ramadhanti; Tahura Malagano; Dina Haryati Sukardi (Universitas Sang Bumi Ruwa Jurai, 2023)
This study discusses and examines the application of the concept of Restorative Justice in the settlement of criminal defamation cases by the Lampung Regional Police Investigator, as well as policies in efforts to apply Restorative Justice in the settlement of criminal defamation cases in the future. The results of research and discussion show that the role of the Investigator of the Cyber Unit of the Lampung Regional Police in the application of restorative justice to criminal defamation cases through social media includes the receipt of complaints. Then it continues in the investigation phase with the qualification of the case, summons, and termination of the investigation. The Restorative justice approach is considered capable of realizing a simple, fast and low-cost justice system, thus further ensuring the fulfillment of legal certainty and community justice. It involves a process whereby all parties at risk in a particular crime jointly seek to collectively resolve how to deal with the aftermath of the crime and its implications in the future. The suggestion in this study is that as law enforcers, investigators at Subdit V Cyber Polri Polda Lampung in this case are expected to hold regular socialization to the public about restorative justice, because there are still many who do not understand the term restorative justice, and it is hoped that the application of restorative justice in Indonesia for criminal defamation cases through social media will get attention More than the government by issuing a clearer legal or regulatory umbrella that criminal defamation can be resolved with a restorative justice approach.